The Changes in Optic Nerve after Orbital Decompression Surgery for Thyroid Eye Disease and Case Reports of Ischemic Optic Neuropathy. (27th February 2022) - Hsia, Yun; Hsiao, Chia-Chieh; Wei, Yi-Hsuan; Lai, I-Wen; Lin, Chao-Wen; Liao, Shu-Lang
Abstract : Purpose. To demonstrate the changes in the retinal nerve fiber layer (RNFL) after orbital decompression for thyroid eye disease (TED). Methods. We retrospectively enrolled 52 surgical TED patients, 30 nonsurgical TED patients, and 30 control subjects. Five surgical TED eyes with disc edema were excluded. The surgical TED patients were classified into the "dysthyroid optic neuropathy (DON)" group (16 eyes) and the "non-DON" group (83 eyes). Optical coherence tomography (OCT) and visual field (VF) examinations were performed preoperatively and 6 months later. The control subjects and nonsurgical TED patients received two OCT examinations at 6-month intervals. The postoperative changes in the RNFL thickness were compared between groups. Three cases with severe postoperative vision loss were presented additionally. Results. The changes in the RNFL thickness of the controls (0.5 ± 3.4 μ m ) and the nonsurgical TED patients (0.3 ± 2.8 μ m ) were significantly smaller than the surgical TED patients (P < 0.001 ). The DON group (− 9.2 ± 9.2 μ m ) had greater RNFL thickness reduction than the non-DON group (− 3.9 ± 5.4 μ m ) (P = 0.002 ). Bone removal decompression was associated with decreased RNFL in the non-DON (P = 0.025 ; β = − 2.49 ) and DON (P = 0.042 ; β = − 9.43 ) groups. Three cases who were hard to operate due to extensive fibrosis experienced severe vision loss postoperatively due to anterior ischemic optic neuropathy, posterior ischemic optic neuropathy, and posterior ciliary artery occlusion, respectively. Conclusions. TED patients experienced subclinical optic nerve injury and significant RNFL loss after the orbital decompression surgery. Aggressive manipulation during decompression surgery may lead to dreadful vision loss. Tailored surgical plans and delicate manipulation are warranted.